Early fractional carbon dioxide laser intervention for postsurgical scars in skin of color - Ibrahim SM; Saudi WM; Abozeid MF; Elsaie ML (Dove Medical Press, 2019)
Shady M Ibrahim,1 Wael M Saudi,2 Mohamed F Abozeid,3 Mohamed L Elsaie4 1Department of Dermatology, Al Azhar University, Cairo, Egypt; 2Department of Dermatology, Misr University for Science & Technology, 6th of October City, Egypt; 3Department of Plastic surgery, Cairo University, Giza, Egypt; 4Department of Dermatology, National Research Centre, Cairo, Egypt Background: Fractional CO2 laser is one of the most effective treatment options used to resurface scars. Objective: To evaluate the efficacy and safety of early treatment of postsurgical scar by fractional ablative CO2 laser. Methods: A total of 27 Egyptian patients with recent postoperative scars were enrolled in this study. Three sessions of fractional CO2 laser with a 1-month interval were started 4 weeks after surgery. Vancouver Scar Scale (VSS) was used as an assessment tool at 1 and 3 months after the final treatment. Patients reported their satisfaction using a subjective 4-point scale. Results: Results demonstrated a statistically significant overall average improvement of the VSS (5.33±1.33) before compared with (2.55±1.06) 3 months after the last laser treatment (P≤0.001). Among the individual parameters in the VSS, the most significant improvements were found in pigmentation, height, and pliability. Patient’s subjective satisfaction scores showed a significant greater degree of satisfaction after laser treatment. Conclusion: Fractional ablative CO2 laser is an effective and safe treatment modality for surgical scars in the early postsurgical period. Keywords: scar, fractional, CO2 laser